Racial Differences in the Association of MIND Diet/Physical Activity Combinations and Cognition in older adults. (20th December 2022) - Holland, Thomas Monroe; Agarwal, Puja; Dhana, Klodian; Desai, Pankaja; Liu, Xiaoran; Krueger, Kristin R; Beck, Todd; Cherian, Laurel J; Schneider, Julie A; Aggarwal, Neelum T.; Barnes, Lisa L.; Rajan, Kumar B
Abstract: Background: Diet and physical activity (PA) are important factors associated with improved cognition. Few studies have investigated the synergistic association with cognitive decline and further, whether the association differs by race. In this study, we investigate whether the observed association of high MIND diet score/high self‐reported PA and cognitive decline is different between African Americans (AA's) and European Americans (EA's). Method: We examined the association of baseline MIND diet and PA combinations on cognition in 3, 657 participants (2206 AAs and 1451 EAs; mean age = 73.2±SD5.8 years) from the Chicago Health and Aging Project. Diet was assessed using a validated 144‐item food frequency questionnaire; self‐reported PA was measured by frequency of engagement in six activities. Cognition was evaluated using a four‐test cognitive battery from which a global composite score and two domains were derived. Participants were followed on average 8.5±SD4.8 years and separated into 9 combinations of MIND diet score and PA (high, moderate, low for MIND diet and high, moderate, low, for PA). Using linear mixed models we examined the rate of cognitive decline; adjusting for age, sex, education, race, ApoE‐4, smoking, and caloric intake. Subsequent models were stratified by race to investigate potential differences in the association of diet and PA combinations with cognitive decline. Result: Participants who reported high MIND/high PA had a slower rate of decline in global cognition (β = 0.015, 24.87% slower, p = 0.007), memory score (β = 0.014, 31.86% slower, p = 0.042) and improved MMSE (β = 0.023, 33.62% improvement, p<0.001) when compared to participants with low MIND/low PA. In race stratified models, we found that in European Americans, high MIND/high PA was associated with slower rates of decline in global cognition (β = 0.028, 37.1% slower, p = 0.007), memory score (β = 0.026, 48.59% slower, p = 0.033) and improved MMSE (β = 0.050, 50.0% improvement, p<0.0001) versus low MIND diet/low PA. However, only an improved MMSE (β = 0.017, 27.11% improvement, p = 0.033) was observed to be associated in African Americans. Conclusion: High adherence to MIND diet/physical activity is associated with slower cognitive decline, regardless of race. However, the breadth of these associations may differ by race. Additional studies are required to elucidate the potential racial differences observed and determine which interventions are most impactful.